Developmental Disabilities and Intracranial Abnormalities in Children with Symptomatic Cytomegalovirus and Cochlear Implants. (13th December 2012) - Hart, Catherine K.; Wiley, Susan; Choo, Daniel I.; Eby, Christine; Tucker, Laura; Schapiro, Mark; Meinzen-Derr, Jareen
Abstract : Objective . To examine the association of intracranial radiographic abnormalities and developmental measures with outcomes in children with congenital symptomatic cytomegalovirus (CMV) and cochlear implants (CI). Design/Methods . It was a retrospective review of 15 children implanted from 2004 to 2010. Preimplant nonverbal intelligence quotient/developmental quotient (IQ/DQ) and head circumference (HC) were obtained. Computed tomography and magnetic resonance imaging of the brain and post-CI audiometry and language assessments were reviewed. Results . Eleven children (73%) had cognitive delay. Most had >1 developmental disability. Median IQ/DQ was 65 (23–90). All had imaging abnormalities. Most imaging abnormalities were in parietal (60%) and temporal (60%) lobes. Children with HC < 5th percentile had poorer median post-CI PTA (38 dB versus 27 dB, P = 0.02 ). Periventricular calcifications were associated with lower receptive (r b = − 0.75, P = 0.03 ) and expressive (r b = − 0.84, P = 0.008 ) language. Because IQ/DQ was associated with periventricular calcifications (r b = − 0.53, P = 0.04 ) and small HC (r b = − 0.73, P = 0.002 ), their relationships with language appear partially driven by IQ/DQ. Conclusions . The location of brain abnormalities appears to correlate with worse outcomes after CI. These findings may allow for more accurate counseling of parents regarding anticipated postimplantation performance.